Epoxy nanocomposites functionalized with in situ generated magnetite nanocrystals: Microstructure, magnetic properties, interaction among magnetic particles. (24th February 2015) - Sciancalepore, Corrado; Bondioli, Federica; Messori, Massimo; Barrera, Gabriele; Tiberto, Paola; Allia, Paolo
Abstract: Magnetite nanoparticles in the range 7–10.5 nm were prepared by non hydrolytic sol–gel (NHSG) process in the presence of benzyl alcohol in different concentrations. The suspensions were mixed with bisphenol A diglycidyl ether (DGEBA) and cured in the presence of ytterbium(III) trifluoromethanesulfonate as cationic initiator. Magnetite nanoparticles and epoxy nanocomposites were characterized by structural, chemical and magnetic techniques. A procedure of data analysis is proposed to determine value, sign and surface contribution of the magnetic anisotropy of nanoparticles by comparing the information gained from field-cooled/zero-field-cooled magnetization curves and TEM images. Above blocking temperature, the nanoparticles dispersed in the epoxy resin give rise to an interacting superparamagnetic system and follow the corresponding scaling law. A model explains why the magnetic interaction energy depends not only on nanoparticle concentration in the epoxy but also on concentration fluctuations, being larger in samples where the nanoparticle dispersion is not uniform. Graphical abstract: